2020
DOI: 10.1111/1467-8268.12430
|View full text |Cite
|
Sign up to set email alerts
|

Financial distress and non‐executive director compensation: Evidence from state‐owned enterprises in South Africa post King III

Abstract: Using a sample of South African state-owned enterprises (SOEs), we examine the pre-and post-period impact of King III on non-executive director (NED) compensation with emphasis on financially distressed SOEs. This paper adopts a difference-indifferences analysis technique with repeated measures as the basis for testing the hypotheses. The revised Altman Z-score model which incorporates features unique to emerging markets is used to measure financial distress. Our findings indicate that SOEs that adopted King I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Inside directors (executive directors) are responsible for managing the companies (management) (Mustapha and Che Ahmad, 2011), while non-executive directors (NEDs) or outside directors serve on behalf of the companies' shareholders. The latter should perform an effective monitoring function to expand their reputations as experts in taking the right monitoring decision (Chen et al, 2020;Emuron and Yixiang, 2020;Fama and Jensen, 1983;Peasnell et al, 2005). Researchers have extensively studied the effect of executive directors' remuneration and EM, some suggesting that executive directors' and CEOs' compensations are associated with higher EM (Park, 2019;Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inside directors (executive directors) are responsible for managing the companies (management) (Mustapha and Che Ahmad, 2011), while non-executive directors (NEDs) or outside directors serve on behalf of the companies' shareholders. The latter should perform an effective monitoring function to expand their reputations as experts in taking the right monitoring decision (Chen et al, 2020;Emuron and Yixiang, 2020;Fama and Jensen, 1983;Peasnell et al, 2005). Researchers have extensively studied the effect of executive directors' remuneration and EM, some suggesting that executive directors' and CEOs' compensations are associated with higher EM (Park, 2019;Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Habbash and Alghamdi, 2015). However, NEDs operate to handle the relationship between shareholders (principals) and agents (management), and NEDs remuneration could boost the quality of monitoring and limit managers' opportunism (Emuron and Yixiang, 2020;Tosi et al, 1997). Thus, investing in outside directors would expect to lead to more effective governance monitoring and advising (Bugeja et al, 2017), which ultimately results in high financial reporting quality.…”
Section: Introductionmentioning
confidence: 99%
“…The research from Mollah et al (2021) on the supervision ability of independent directors showed that the greater the difference of independent directors, the more effective their supervision were. Emuron and Tian (2020) found that when the board of directors had members who serve in financial institutions, it was often more unlikely for companies to get into financial distress. Because they cannot only benefit the company through professional knowledge, skills, etc., but also gain potential financing advantages through their personal network.…”
Section: Literature Reviewmentioning
confidence: 99%